2008
DOI: 10.12973/ejmste/75301
|View full text |Cite
|
Sign up to set email alerts
|

Reform-Based Science Teaching: Teachers’ Instructional Practices and Conceptions

Abstract: This study aimed at exploring the practices and beliefs physics teachers have about introducing reform-based instruction into the physics class. Data were collected from semi-structured interviews held with 11 experienced physics teachers. The results revealed that the teachers occasionally introduced a small number of enhanced instructional strategies explicitly required by the formal curriculum into their class, such as presenting, analyzing and generalizing experimental results in different forms. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Based on the NSES (NRC, 1996) (NRC, 1996(NRC, , 2012. Research evidence showed that using inquiry-based instructional approach was beneficial to promote students" understandings of the content taught and their learning outcomes in diverse subject areas and various grade levels (Akerson & Hanuscin, 2007;Barak & Shakhman, 2008;Fishman et al, 2003;Lin, et al, 2014;Luft, 2001;Marx, et al , 2004;Santos-Trigo, 2008). Espinosa-Bueno et al (2011) confirmed the effects of inquiry-based teaching, and that it enabled students to develop habits of observation and reasoning.…”
Section: Theoretical Framework Scientific Inquirymentioning
confidence: 99%
“…Based on the NSES (NRC, 1996) (NRC, 1996(NRC, , 2012. Research evidence showed that using inquiry-based instructional approach was beneficial to promote students" understandings of the content taught and their learning outcomes in diverse subject areas and various grade levels (Akerson & Hanuscin, 2007;Barak & Shakhman, 2008;Fishman et al, 2003;Lin, et al, 2014;Luft, 2001;Marx, et al , 2004;Santos-Trigo, 2008). Espinosa-Bueno et al (2011) confirmed the effects of inquiry-based teaching, and that it enabled students to develop habits of observation and reasoning.…”
Section: Theoretical Framework Scientific Inquirymentioning
confidence: 99%
“…Curricula are also usually decontextualised, focusing on knowledge without a "real life" meaning to students (Makrakis & Kostoulas-Makrakis, 2005). These discrepancies seem to be not only an outcome of the difficulty translating constructivism in curriculum development and teaching practice, but also of the misleading conception of constructivism as a homogeneous philosophy (Dancy & Henderson, 2007;Barak & Shakhman, 2008). The view that constructivism is synonymous with approaches to teaching that are learner-centred based on the utilisation of previous knowledge is misleading.…”
Section: The Mainstream or Reformist Viewmentioning
confidence: 99%
“…The effective implementation of research-validated instructional strategies will be referred to as reformed instruction (see MacIsaac and Falconer 2002). Despite the evidence in favor of the adoption of reformed teaching methods, many instructors in K-12 and higher education institutions have been reluctant to adopt these new strategies (Barak and Shakhman 2008;Henderson and Dancy 2007) and participation in professional development may be insufficient to promote the transition of these alternative approaches to instruction (e.g., Ebert-May et al 2011). University faculty members report several barriers to instructional reform including limited training, insufficient time, and lack of instructional and peer support (Dancy and Henderson 2010;Fairweather 2010;Henderson and Dancy 2007;Sunal et al 2001;Wieman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research on this subject has occurred in K-12 or pre-service settings and examined instructors' beliefs regarding their roles in the classroom, how students learn best, and the most effective types of student-instructor interactions (Barak and Shakhman 2008;Fang 1996;Fishbein and Ajzen 1975;Hake 1998;Jones and Carter 2007;Kagan 1992;Luft and Roehrig 2007;Richardson 1996). Beliefs affect action (Guskey 1986;Hashweh 1996;Kang and Wallace 2005) and any steps seeking to promote lasting classroom change must consider a teacher's pedagogical beliefs (Barak and Shakhman 2008;Guskey 1986;Luft and Roehrig 2007). Successfully shifting the pedagogical beliefs of instructors toward a reformed mindset is essential if professional development is to positively influence teaching in STEM classrooms (Keys and Bryan 2001).…”
Section: Introductionmentioning
confidence: 99%